2007
DOI: 10.1021/nl0705438
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-Modulated Ion Fluxes through Peptide-Nucleic-Acid- Functionalized Gold Nanotubes. A New Approach to Quantitative Label-Free DNA Analysis

Abstract: The inner walls of gold nanotubules, prepared by template synthesis in the nanopores of polycarbonate track etch membranes, have been chemically modified with peptide nucleic acid (PNA) and used for label-free quantification of complementary DNA sequences. Selective binding of DNA to the PNA modified nanotubules are shown to decrease the flux of optically detected anionic markers through the nanotubules in a concentration-dependent manner. The strong dependence of the biorecognition-modulated ion transport thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 22 publications
(49 reference statements)
2
66
0
Order By: Relevance
“…We aimed to simulate the reaction mechanism of both the native and the evolved enzyme and compare the major catalytic factors. The activation barriers obtained by the Empirical Valence Bond (EVB) method [3] were in accord with the experimental data. We found that in course of the laboratory evolution the reorganization energy was optimized significantly, meanwhile the activation barrier only modestly decreased.…”
Section: Scheme 2 Novel Methods For the Preparation Of Phosphinatessupporting
confidence: 67%
See 1 more Smart Citation
“…We aimed to simulate the reaction mechanism of both the native and the evolved enzyme and compare the major catalytic factors. The activation barriers obtained by the Empirical Valence Bond (EVB) method [3] were in accord with the experimental data. We found that in course of the laboratory evolution the reorganization energy was optimized significantly, meanwhile the activation barrier only modestly decreased.…”
Section: Scheme 2 Novel Methods For the Preparation Of Phosphinatessupporting
confidence: 67%
“…Sensing with nanopores/nanotubes for molecular detection emerged recently in the forefront of nanostructure-based chemical sensors [1] due to its potential for: (a) ultrafast DNA sequencing; [2] (b) biosensing with selective receptor modified nanopores; [3] (c) macromolecule and nanoparticle counting [4]. Sensing with nanopores most often implies monitoring changes in the applied voltage driven ion flow across a nanopore that separates two electrolyte chambers as particles are passing through or residing within the nanopore sensing zone.…”
Section: Modeling the Response Of Single-nanopore Electrochemical Biomentioning
confidence: 99%
“…As with redox indicators, the diffusion of an optical indicator can be measured through a nanoporous membrane (Jágerszki et al, 2007). Such sensing schemes can potentially take advantage of distinctive recognition/transport phenomena that occur in nanostructures.…”
Section: Other Detection Methodsmentioning
confidence: 99%
“…Additionally, PNA probes have excellent chemical, biochemical and thermal stability. Their electroneutrality makes them ideal probes for electrochemical transducers based on detection of surface charge variations upon oligonucleotide hybridization, e.g., ion channel sensors [31], field effect transistors (FET) [31], and nanopore sensors [32,33]. As a low cost alternative of PNA, antisense morpholino oligos (MCPs), which have higher affinity to complementary RNA than natural nucleic acid probes, were also reported [34].…”
Section: Selective Probes For Mirna Detectionmentioning
confidence: 99%